The "Dušan Bandić" Award for 2007 to Dragana Antonijević - Editorial Board (Etnoantropološki Problemi, 2016)
The recipient of the award was dr Dragana Antonijević, assistant professor at the Faculty of Philosophy, University of Belgrade for the book "Karađorđe i Miloš: Mit i politika" [Karadjordje and Milos: Myth and Politics], Beograd 2007, Srpski genealoški centar - Odeljenje za etnologiju i antropologiju Filozofskog fakulteta, Etnološka biblioteka 33